2010
DOI: 10.1007/s10706-010-9303-y
|View full text |Cite
|
Sign up to set email alerts
|

Longwall Face Stability Index for Estimation of Chock-Shield Pressure and Face Convergence

Abstract: The paper discusses the concept and methodologies for the development of longwall face stability index (LFSI). LFSI is used for estimation of chock-shield pressure and face convergence. The index comprises of engineering properties of main roof, depth of mining, different support capacities and mechanical properties of coal seam being mined and provides a numerical value in the range of -6.17 to 8.13. In this study, 324 finite element models of longwall panel are developed based on various combinations of geom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…Yun et al [17] clearly showed that the front leg pressure was greater than the rear leg pressure in another China longwall face (Figure 8a). The difference between front leg and rear leg pressures was also seen in India's longwall panels, as reported by Verma and Deb [18] (Figure 8b) and Singh and Singh [19]. During the time of monitoring, coal face was, in general, stable.…”
Section: Resultssupporting
confidence: 73%
“…Yun et al [17] clearly showed that the front leg pressure was greater than the rear leg pressure in another China longwall face (Figure 8a). The difference between front leg and rear leg pressures was also seen in India's longwall panels, as reported by Verma and Deb [18] (Figure 8b) and Singh and Singh [19]. During the time of monitoring, coal face was, in general, stable.…”
Section: Resultssupporting
confidence: 73%
“…Based on the above-mentioned theories, a series of studies on the interaction mechanism between hydraulic support and the roof strata has been performed. A. K. Verma and D. Deb [24,25] developed an index considering the wide variations of geomining parameters to ascertain the chock shield pressure and face convergence. They found that the mechanical parameters of the main roof and coal seam were closely related to the load on the front leg of the chock-shield support.…”
Section: Introductionmentioning
confidence: 99%
“…The calculation models of the working resistance of the support under different movement types were established in succession, and the onsite measurement data were verified. Verma and Deb [13,14] modified the load estimation method according to the structural characteristics of overlying strata of a working face under hard roof conditions and acquired the computation method for the working resistance of hydraulic supports on a fully mechanized caving face for a thick coal seam under hard roof condition. The hanging arch length of the key strata on the roof and the influence factors of its caving and fracturing were obtained by combining the theoretical analyses of the cantilever beam.…”
Section: State Of the Artmentioning
confidence: 99%
“…According to the theory of mechanics of materials, the moment acted by the hard rock strata on the lower rock strata within the scope of the roof control zone in Eq. (12) can be expressed as (13) Eq. (13) is then substituted with Eq.…”
Section: Support-surrounding Rock Relation Under Movement Instabilitymentioning
confidence: 99%